Exodus: How Migration is Changing Our World (an excerpt) - Paul Collier (Journal of Economic Sociology, 2015)
In his book Exodus: How Migration is Changing Our World, Prof. Collier continues economic research on the poorest nations in the contemporary world. The author focuses on consequences of immigration flows from poor developing countries to rich developed ones. To study migration, Collier raises three questions: (1) why do migrants decide to move from one country to another? (2) does emigration benefit or harm people who decide not to leave their home country? (3) what impact do migrants produce on host country citizens? In his search for answers to these questions, Professor Collier summarizes original research and case studies.Journal of Economic Sociology presents Chapter 1, “The Migration Taboo,” in which Professor Collier defines the research problem and argues that scholars tend to avoid migration issues related to movements of people from poorer countries to richer ones as a focal point of their research. The reason for such avoidance is that this topic is strongly associated with socially explosive issues related to nationalism and racism. However, the author points out one possible way to deal with migration issues, implying reconsideration of the key question for research on migration, namely — not to think of migration in terms of good or bad but to aim at defining the optimality of migration flows for both sending countries and receiving countries.